2015
DOI: 10.1177/2050312114565198
|View full text |Cite
|
Sign up to set email alerts
|

Is objective and accurate cognitive assessment across the menstrual cycle possible? A feasibility study

Abstract: Objectives:Variation in plasma hormone levels influences the neurobiology of brain regions involved in cognition and emotion processing. Fluctuations in hormone levels across the menstrual cycle could therefore alter cognitive performance and wellbeing; reports have provided conflicting results, however. The aim of this study was to assess whether objective assessment of cognitive performance and self-reported wellbeing during the follicular and luteal phases of the menstrual cycle is feasible and investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…These changes are noteworthy because low MF and IAF values are often observed in patients with cognitive dysfunction and dementia ( Poza et al, 2007 ). Previous studies have indicated that some cognitive functions are impaired during the MP, including mental rotation, visuospatial ability, verbal memory, and verbal fluency, although these findings remain controversial ( Sommer, 1992 ; Schöning et al, 2007 ; Hatta and Nagaya, 2009 ; Poromaa and Gingnell, 2014 ; Farrar et al, 2015 ; Sundström-Poromaa, 2018 ). Low values of MF and IAF during the MP may reflect impairments in cognitive function due to the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are noteworthy because low MF and IAF values are often observed in patients with cognitive dysfunction and dementia ( Poza et al, 2007 ). Previous studies have indicated that some cognitive functions are impaired during the MP, including mental rotation, visuospatial ability, verbal memory, and verbal fluency, although these findings remain controversial ( Sommer, 1992 ; Schöning et al, 2007 ; Hatta and Nagaya, 2009 ; Poromaa and Gingnell, 2014 ; Farrar et al, 2015 ; Sundström-Poromaa, 2018 ). Low values of MF and IAF during the MP may reflect impairments in cognitive function due to the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The most accurate measures are biological measures such as blood or saliva samples where hormone levels are directly assessed. Alternatively, self-report measures can be used, however, this might not be an accurate or consistent measure (Farrar et al, 2015).…”
Section: The Ovarian Cyclementioning
confidence: 99%
“…While the most accurate method would be to measure hormone levels in the blood of the participant at the point of auditory testing, most previous work has used selfreported measures. However, we know that self-report measures are less accurate that biological assessment at estimating levels of estradiol in the bloodstream (Farrar et al, 2015), yet studies using either method are treated as comparable. This can make is difficult to develop a clear understanding of how sex hormones affect the various stages of the auditory pathway in an overall and cyclical fashion.…”
Section: Contribution To the Fieldmentioning
confidence: 99%